Empire's Law : The American Imperial Project and the 'War to Remake the World' - Edited by Bartholomew, Amy (London Pluto Press, 2006)
What is the legacy of the war in Iraq? Can democracy and human rights really be imposed "by fire and sword"? This book brings together some of the world's most outstanding theorists in the debate over empire and international law. They provide a uniquely lucid account of the relationship between American imperialism, the use and abuse of "humanitarian intervention", and its legal implications. Empire's Law is ideal for students who want a comprehensive critical introduction to the impact that the doctrine of pre-emptive war has had on our capacity to protect human rights and promote global justice. Leading contributors including Leo Panitch, Sam Gindin, Jurgen Habermas, Ulrich Preuss, Andrew Arato, Samir Amin, Reg Whitaker, Denis Halliday and Hans von Sponeck tackle a broad range of issues. Covering everything from the role of Europe and the UN, to people's tribunals, to broader theoretical accounts of the contradictions of war and human rights, the contributors offer new and innovative ways of examining the problems that we face. It is essential reading for all students who want a systematic framework for understanding the long-term consequences of imperialism.
Include Notes and Index.
The American Imperial Project and the 'War to Remake the World.'
Keywords: Military policy -- United States -- Diplomatic relations -- United Nations -- Globalization -- Imperialism -- International law -- Iraq